Hetero Diels–Alder Reactions with a Dicationic Urea Azine Derived Azo Dienophile and Their Use for the Synthesis of an Electron‐Rich Pentacene - Werr, Marco (Chemistry, 2020)
Herein, the first hetero Diels–Alder (DA) reactions with a stable, dicationic urea azine derived azo dienophile, synthesized by two‐electron oxidation of a neutral urea azine are reported. Several charged DA products were synthesized in good yield and fully characterized. The DA adduct of anthracene is in thermal equilibrium with the reactants at room temperature, and the reaction enthalpy and entropy were determined from the temperature‐dependent equilibrium constant. Furthermore, base addition to solutions of the pentacene DA product led to deprotonation, cleavage of the N−N bond, and formation of an electron‐rich 6,13‐bisguanidinyl‐substituted pentacene. The redox and optical properties of this new pentacene derivative were studied. Furthermore, the dication resulting from its two‐electron oxidation was synthesized and fully characterized. The results disclose a new elegant route to electron‐rich pentacene derivatives.